The association of parental monitoring and parental communication with sexual and substance use risk behaviors among Native American Youth. (October 2021) - Patel, Hima; Chambers, Rachel; Littlepage, Shea; Rosenstock, Summer; Richards, Jennifer; Lee, Angelita; Slimp, Anna; Melgar, Laura; Lee, Shauntel; Susan, Davette; Tingey, Lauren
Highlights: Parental monitoring and communication reduce sexual behavior of Native youth. Parental monitoring and communication reduce substance use behavior of Native youth. Youth programs involving parents reinforces value of family in Native communities. Abstract: Context: Native American (Native) youth face high rates of substance use, teen pregnancy and sexually transmitted infections. Native communities are strengthened by values of family, yet limited research exists examining the associations between parental communication, monitoring and these risk behaviors. Methods: Analyses of a c ross-sectional sample of Native youth ages 11–19 examined associations between youth and parental communication, parental monitoring and sexual and substance use behaviors. Logistic regressions, controlled by age, were performed in sex-specific bivariate models and multivariate models. Results: N = 543 youth were enrolled. Bivariable analyses: Female youth with greater parental communication about sex were significantly less likely to report intention to use marijuana. Female youth with high parental monitoring were significantly less likely to report intention to drink alcohol or have sex; they were significantly less likely to have ever smoked, used marijuana, or had vaginal sex. Male youth were significantly more likely to report intention to use a condom if they had higher parental communication, higher parental communication about sex and higher parental monitoring. Multivariable analyses: Female youth with greater parental communication were significantly less likely to ever have drank alcohol. Female youth with high parental monitoring were significantly less likely to report intentions to drink alcohol or have sex; they were also significantly less likely to have ever smoked, used marijuana, or had vaginal sex. Among male youth, intention to use condoms was significantly higher for those with high parental communication and high parental monitoring. Conclusions: Positive associations between parental monitoring, parental communication and reduced youth risk-taking show that families, parents and trusted adults are a meaningful and crucial protective factor against high risk substance and sexual behaviors and should be included in prevention programming for Native youth. Parental monitoring and communication impacted genders differently, suggesting that the quality and depth of communication surrounding substance use and sex may vary widely between families, community and Native cultures and by youth gender.